Spatio-Temporal Representativeness of Air Quality Monitoring Stations in Mexico City: Implications for Public Health - Baca-López, Karol; Fresno, Cristóbal; Espinal-Enríquez, Jesús; Martínez-García, Mireya; Camacho-López, Miguel Angel; Flores-Merino, Miriam V.; Hernández-Lemus, Enrique (Frontiers in Public Health, 2021)
Assessment of the air quality in metropolitan areas is a major challenge in environmental sciences. Issues related include the distribution of monitoring stations, their spatial range or missing information. In Mexico City, stations have been located spanning the entire Metropolitan zone for pollutants such as CO, NO2, O3, SO2, PM_2.5, PM_10, NO, NO_X, and PM_CO. A fundamental question is whether the number and location of such stations are adequate to optimally cover the city. By analyzing spatio-temporal correlations for pollutant measurements, we evaluated the distribution and performance of monitoring stations in Mexico City from 2009 to 2018. Based on our analysis, air quality evaluation of those contaminants is adequate to cover the 16 boroughs of Mexico City, with the exception of SO2, since its spatial range is shorter than the one needed to cover the whole surface of the city. We observed that NO and NO_X concentrations must be taken into account since their long-range dispersion may have relevant consequences for public health. With this approach, we may be able to propose policy based on systematic criteria to locate new monitoring stations.